Controlling iron versus oxygen redox in the layered cathode Na0.67Fe0.5Mn0.5O2: mitigating voltage and capacity fade by Mg substitution - Boivin, E; House, RA; Marie, J-J; Bruce, PG (Wiley, 2022)
Layered oxides for Na-ion batteries containing Fe have attracted strong interest mainly due to their low cost. However, full oxidation of Fe3+ to Fe4+ is rarely seen before O-redox sets in and is typically accompanied by voltage and capacity fade on cycling. On charging P2-Na0.67[Fe0.5Mn0.5]O2, Fe3+ is oxidized to only ≈Fe3.3+ before the onset of O-redox. O-redox occurs when the Na content is sufficiently low (Na ≈0.3) to permit the transition from P-type to O-type stacking, thus enabling Fe3+ migration to the Na layer. Fe3+ migration generates cation vacancies in the transition metal layer, forming □-O-□ configurations, which trigger the onset of O-redox. In contrast, doping this material with Mg2+ to form P2-Na0.67[Fe0.25Mn0.6Mg0.15]O2 allows full oxidation of Fe3+ to Fe4+ before the Na content is low enough to favor O-type stacking. During O-redox, Mg2+ is displaced into the Na layers instead of Fe. Mg substitution enables greater reversibility of the Fe3+/Fe4+ redox couple and significantly suppresses Fe migration, which is responsible for the voltage and capacity fade observed for P2-Na0.67Fe0.5Mn0.5O2.